2014
DOI: 10.1097/jpn.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Information on Fetal Heart Rate Monitoring During Labor

Abstract: Electronic fetal monitoring (EFM) is used for the majority of births that occur in the United States. While there are indications for use of EFM for women with high-risk pregnancies, its use in low-risk pregnancies is less evidence-based. In low-risk women, the use of EFM is associated with an increased risk for cesarean birth compared with the use of intermittent auscultation of the fetal heart rate. The purpose of this investigation was to evaluate the existence of evidence-based information on fetal heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…32 Involving low-risk laboring women in shared decision making and offering informed choice about mode of fetal monitoring may further add to their satisfaction with the experience of labor and birth. 33,34 Since IA requires a ratio of one care provider to one woman and near constant presence in order to perform auscultation at the recommended frequency, this method of fetal surveillance during labor may also contribute to improved outcomes and increased patient satisfaction. 35…”
Section: Patient Satisfaction and Choicementioning
confidence: 99%
See 1 more Smart Citation
“…32 Involving low-risk laboring women in shared decision making and offering informed choice about mode of fetal monitoring may further add to their satisfaction with the experience of labor and birth. 33,34 Since IA requires a ratio of one care provider to one woman and near constant presence in order to perform auscultation at the recommended frequency, this method of fetal surveillance during labor may also contribute to improved outcomes and increased patient satisfaction. 35…”
Section: Patient Satisfaction and Choicementioning
confidence: 99%
“…In a systematic review of factors contributing to women's satisfaction with the experience of childbirth (N = 45,000), investigators identified the 4 most important factors: personal expectations, amount of caregiver support, quality of caregiver support, and involvement in decision making . Involving low‐risk laboring women in shared decision making and offering informed choice about mode of fetal monitoring may further add to their satisfaction with the experience of labor and birth . Since IA requires a ratio of one care provider to one woman and near constant presence in order to perform auscultation at the recommended frequency, this method of fetal surveillance during labor may also contribute to improved outcomes and increased patient satisfaction …”
Section: Documentationmentioning
confidence: 99%
“…Analyses carry implications for maternity care providers’ communication of STan to consumers; specifically, how STan is intended to alert clinicians to problems in labour before they escalate, rather than respond to problems after they become emergencies [ 6 ]. This may be important given results of a previous study that reported variable accuracy in the content of consumer-focused maternity information about fetal monitoring [ 33 ].…”
Section: Discussionmentioning
confidence: 99%